Evaluation of antibodies to oxidized low-density lipoprotein and assessment of C-reactive protein in acute coronary syndrome and stable coronary artery disease - Soltesz, Pal; Veres, Katalin; Laczik, Renata; Der, Henrietta; Csipo, Istvan; Timar, Orsolya; Szomjak, Edit; Szegedi, Gyula; Szodoray, Peter (Thrombosis and Haemostasis, 2007)
The aim was to measure the level of antibodies to oxidized LDL (oxLDL) and C-reactive protein (CRP) in the serum of patients with acute coronary syndrome (ACS). The results were correlated with data obtained from patients with stable coronary artery disease (stable CAD) and healthy controls.Thirty-three patients with ACS and 62 stable CAD patients were enrolled in the study. Fifty healthy individuals served as controls.The evaluation of anti-oxLDL autoantibodies was performed by ELISA, while CRP levels were measured by turbidimetry. The level of antibodies to oxLDL was significantly higher in both groups of patients with ACS and stable CAD compared to controls.The comparison between the acute and stable groups showed that anti-oxLDL levels were higher in the acute group,but because of high SD, the difference was not significant. By performing group analysis, anti-oxLDL levels were found to be significantly higher in ACS patients with unstable clinical state (circulatory insufficiency, malignant arrhythmias, recurring ischemic pain, need for urgent coronary intervention and death). CRP level in patients with ACS was significantly higher than in those with stable CAD. A positive correlation was found between anti-oxLDL antibodies and CRP levels both in patients with ACS and stable CAD. The association between the two biomarkers was stronger in the ACS group. In conclusion, our findings support the notion that the presence of antibodies to oxLDL, a plaquespecific antigen, plays a major role as a predictor of complicated manifestations of ACS.
Keywords: Atherosclerosis; coronary artery disease; antibodies to oxidized LDL; C-reactive protein